1. dê o valor de cada uma das expressões:
a)
![\sqrt[6]{(2x)} {}^{6 } = \sqrt[6]{(2x)} {}^{6 } =](https://tex.z-dn.net/?f=+%5Csqrt%5B6%5D%7B%282x%29%7D+%7B%7D%5E%7B6+%7D+++%3D+)
b)
![\sqrt[3]{7 {}^{3} } = \sqrt[3]{7 {}^{3} } =](https://tex.z-dn.net/?f=+%5Csqrt%5B3%5D%7B7+%7B%7D%5E%7B3%7D+%7D++%3D+)
2. escreva na forma mais simples possível:
a)
![\sqrt[4]{ \sqrt[3]{64} } = \sqrt[4]{ \sqrt[3]{64} } =](https://tex.z-dn.net/?f=+%5Csqrt%5B4%5D%7B+%5Csqrt%5B3%5D%7B64%7D+%7D++%3D+)
b)
![\sqrt{ \sqrt[5]{243} } = \sqrt{ \sqrt[5]{243} } =](https://tex.z-dn.net/?f=+%5Csqrt%7B+%5Csqrt%5B5%5D%7B243%7D+%7D++%3D+)
Soluções para a tarefa
Respondido por
1
Resposta:
vide resolução
Explicação passo-a-passo:
1.
a)
b)
2.
a)
b)
Perguntas interessantes
Biologia,
10 meses atrás
Biologia,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Espanhol,
1 ano atrás